The major risk factors for coronary artery disease in the Coloureds of the Cape Peninsula : The CRISIC Study - Steyn, Krisela (Department of Public Health and Family Medicine, 2018)
A cross-sectional study of risk factors for coronary heart disease (CHD) in a random sample of 976 coloured people revealed a population greatly at risk of CHD. The major reversible risk factors were very common: 57% of men and 41% of women smoked, 17,2% of men and 18,4% of women were hypertensive (>160/95 mm Hg or receiving medication), and 17,4% of men and 16,2% of women had a total serum cholesterol value above 6,5 mmol/litre. The high cut-off points used to identify the above prevalence rate do not reflect the total population at risk. At lower but real levels of risk 94,6% of men and 89,8% of women carried some degree of CHD risk factors was found.